If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + 6 = 12 Reorder the terms: 6 + q = 12 Solving 6 + q = 12 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + q = 12 + -6 Combine like terms: 6 + -6 = 0 0 + q = 12 + -6 q = 12 + -6 Combine like terms: 12 + -6 = 6 q = 6 Simplifying q = 6
| X^2-16x+54=-9 | | 3(7k-7)=-168 | | c^2-8ct+16t^2= | | (4.5)y=x+6 | | 3x^2-7= | | 5/4x-2/3y=1 | | -28+n=-39 | | -2/3x5/4 | | 5x+7x=7x+5 | | 72/82*49/82= | | 3=1.5b+11 | | y^2=-45+14y | | lny=16x+lnC | | 8+12m+9=-50m+45 | | -15x^2-40x=-20x^2-8x | | 1/4z2 | | -3.08/-0.2=15.4 | | 6/7*(-7/1)= | | 19-y=6 | | f(x)=-8x^2-5 | | 25=-2 | | -5(-3u+7)-7u=2(u-9)-3 | | 2=5x-1+b | | 4*(-7/8)= | | -4x+6x+10=-2x-5+15 | | c-(y+2)=3y | | 24(3x^2+4)=0 | | 25y-40=20y-80 | | d/9.7=2.08 | | 4x+3(13)+7=4x+4(13)-6 | | 7-1.1k=32 | | -2(7n-2)-3(4+4n)=n-8+5n |